PERFORMA AYAM KUB UNSEX PERIODE FINISHER (9--12 MINGGU) PADA PEMBERIAN RANSUM DENGAN KADAR PROTEIN BERBEDA - Irawan, Hery; Tantalo, Syahrio; Nova, Khaira (Jurnal Riset dan Inovasi Peternakan, 2018)
This aim of this study was determine the effect of different crude protein in the ration on performance KUB chicken finisher period.  This study used Completely Randomized Design (CRD) with 3 treatments and 8 replications, each replication consisted of 4 chickens (unsex) 9 weeks old with 9,33% diversity coefficient.  The study was conducted for 4 weeks in July 2017--August 2017 at the cage of B Field Integrated Laboratory, Faculty of Agriculture, University of Lampung.  The treatment given in this study was diet with crude protein content R0: 14,13%, R1: 11,30% and R2: 8,38% with 8 replication, each replication consisted of 4 chickens.  The variables observed were ration consumption, protein consumption, body weight gain, ration conversion, and income over feed cost.  The results showed that ration with different crude protein content were influential not significantly (P> 0,05) to ration consumption, protein consumption, body weight gain, ration conversion, and income over feed cost of KUB chicken finisher period. Keywords: Performance, Chicken KUB, period finisher, ration, crude protein.